A novel variant in FOXC1 associated with atypical Axenfeld-Rieger syndrome - Rui Wang (BMC, 2021)
Abstract Mutations in the Forkhead Box C1 (FOXC1) are known to cause autosomal dominant hereditary Axenfeld-Rieger syndrome, which is a genetic disorder characterized by ocular and systemic features including glaucoma, variable dental defects, craniofacial dysmorphism and hearing loss. Due to late-onset of ocular disorders and lack of typical presentation, clinical diagnosis presents a huge challenge. In this study, we described a pathogenic in-frame variant in FOXC1 in one 5-year-old boy who is presented with hypertelorism, pupil deformation in both eyes, conductive hearing loss, and dental defects. By whole exome sequencing, we identified a 3 bp deletion in FOXC1, c.516_518delGCG (p.Arg173del) as the disease-causing variant, which was de novo and not detected in the parents, and could be classified as a “pathogenic variant” according to the American College of Medical Genetics and Genomics guidelines. After confirmation of this FOXC1 variant, clinical data on Axenfeld-Rieger syndrome-associated clinical features were collected and analyzed. Furthermore, Although the affected individual present hearing loss, however, the hearing loss is conductive and is reversible during the follow-up, which might not linke to the FOXC1 variant and is coincidental. Routine examination of FOXC1 is necessary for the genetic diagnosis of hypertelorism-associated syndrome. These findings may assist clinicians in reaching correct clinical and molecular diagnoses, and providing appropriate genetic counseling.